Problems of Iran's Economic Policy: The Rivalry of Conservatives and Reformists in Iran - Afini Nurdina Utami; M. Hamdan Basyar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
There are differing interests of the conservative and reformist camps in Iran's economic policy. The conservative camp wants Iran's economic system to run according to the ideals of the early revolution which rejected the Western system in implementing economic policies. Meanwhile, the reformist camp wants Iran's economic policies to follow the neoliberal concept. These policy changes along with the changes of Iranian Presidents, it has caused policy differences resulting in Iran having an unstable economy. This study wants to answer why the Iranian economy is unstable. This research uses a descriptive qualitative method through literature review. The results can be concluded that the factors that influence Iran's changing economic policies are rooted in the internal problems of the government institutions in Iran.